THE KEY TO MINIMIZE MISCALCULATION OF OIL/CONDENSATE - QAS (QUANTITY ACCOUNTING SYSTEM) BY APPLYING ASTM PROVISIONS - Onnie Ridaliani (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
The Petroleum Industry does not only consist of exploration and exploitation activities, but there are other activities that are also important, namely lifting activities. The lifting activity is one of the transfer/ shipping activities from upstream (Producer) to downstream (Buyer). One of the lifting activities is the calculation of the amount of oil/condensate, which is a calculation of the calculation and reporting of oil/condensate that is applied in managing the distribution of oil/condensate production from the block station to the point of sale. The importance of this calculation system is due to the amount of lifting that will be reported to the state. This needs to be done well to avoid the wrong amount of value. ASTM (American Society for Testing and Materials) is an international organization that develops and publishes technical standards for various materials, products, systems and services. The lifting job based on the conditions established by ASTM can minimize the possibility of errors in calculation of QAS (Quantity Accounting System), in this case specifically for fluid level measurements in tanks, temperature measurements, methods and techniques for measuring the number of samples, proving job, laboratory analysis (such as Density, BS&W, etc), and the methods that must be used (Flow Meter or Meter Tank Gauging) for QAS input. This paper is made using reference activities that happen in lifting points in Riau Province, North Sumatra Province, and Aceh Province. It is expected to provide more understanding of the necessary of applying the ASTM provisions to lifting activities.